The Human Nervous System 2012
DOI: 10.1016/b978-0-12-374236-0.10008-2
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Brainstem Nuclei

Abstract: This chapter describes human homologs of nuclei identified in the brainstem of other mammals and attempts to extend to the human the overall organizational schemata that have been proposed for the brainstem of other mammalian species. We present herein updated diagrams of the Atlas of the Human Brainstem (Paxinos and Huang, 1995). The diagrams have been thoroughly revised in light of our recent work on the rat (Paxinos and Watson, 2007) and rhesus monkey (Paxinos et al., 3rd ed, in BrainNavigator, Elsevier, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
196
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(210 citation statements)
references
References 170 publications
(186 reference statements)
14
196
0
Order By: Relevance
“…A – F Right dorsal quadrant of caudal medulla oblongata sections immunostained for CGRP and counterstained with Kluver-Barrera. A 1 – F 1 diagrams modified from Paxinos et al (2012) at levels indicated as distance from obex, matching those shown in A – F . Gray matter regions endowed with CGRP immunoreactivity and located medially ( B ), dorsally ( C , E ) and laterally ( D , E ) in the cuneate fascicle (cu) near the cuneate nucleus (Cu) border are encircled in red.…”
Section: Resultssupporting
confidence: 67%
“…A – F Right dorsal quadrant of caudal medulla oblongata sections immunostained for CGRP and counterstained with Kluver-Barrera. A 1 – F 1 diagrams modified from Paxinos et al (2012) at levels indicated as distance from obex, matching those shown in A – F . Gray matter regions endowed with CGRP immunoreactivity and located medially ( B ), dorsally ( C , E ) and laterally ( D , E ) in the cuneate fascicle (cu) near the cuneate nucleus (Cu) border are encircled in red.…”
Section: Resultssupporting
confidence: 67%
“…These histological images were courtesy of the Brain Biodiversity Bank of the Michigan State University 2 , 3 with support from the US National Science Foundation. An experienced neuroanatomist (UB; experience more than 15 years) assessed the MR images and identified anatomical structures and substructures if they coincided with a histoarchitectonic atlas (Bergman et al, 1989; Naidich et al, 2009; Paxinos et al, 2012) and if they were identifiable with respect to the surrounding tissue. For this qualitative analysis the window and level settings of the MR images were adjusted freely.…”
Section: Methodsmentioning
confidence: 99%
“…The mesencephalic reticular formation (MRF) which is mainly composed by the pedunculopontine (PPN) (also renamed the pedunculotegmental nucleus by Paxinos et al (2012) and the cuneiform nuclei is thought to be involved at least in two fundamental brain functions: locomotion and waking state.…”
Section: Introductionmentioning
confidence: 99%